Pendistribusian Sumber Daya Air Di Pulau Jemara - Widodo; Nidia Yuniarsih; Hanifah Widiastuti; Domi Kamsyah; Adi S.P; Ninda H.B (Politeknik Caltex Riau, 2022)
Water demand is the amount of water required to support human activities. Along with the growth ofJemara Island comunity, water has became one of the primary need to obtain a better and productive life.According to the survey that has been carried out, Jemara Island community still have not had access for cleanwater and electricity to accommodate the community need. Based on the results of field survey, Jemara Islandcomunity rely their water need on seven dug wells with diameter of each well of 1,5 meters and depth of 3meters. However, at high tide, the well near to residential will be affected. It causes Jemara Island communityrely in their water supply on the well 10 meter away from the residential which spend lot of energy. Therefore,this service community program will optimize two wells located far from the shoreline at the top of thetopography, provided water pump to drawn well water, provide water reservoir and also install pipe waterdistribution to the residential. According to a study that has been carried out, to drain water into two reservoirswith a capacity of 2,500 liters, the pump is able to operate for 6 hours with 2 hours pause after used to avoidpump perform over the daily usage limit. In order to pump water to the reservoirs, it needs 6 liters gasoline tooprate the pump and generator set. Assuming that each resident consumes 10 liters of water per day with apopulation of 150 people, then the need for clean water for drinking or cooking is 1500 liters, so it is estimatedthat two tandons will be used for about 4-5 days.